Multiplication and division of fractions based on numerical literacy electronic module for fifth grade elementary school students - Dyah Triwahyuningtyas; Nyamik Rahayu Sesanti; Emi Firdayanti; Ni'matul Aziza (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2022)
This research is motivated by the need to provide teaching materials in the form of electronic-based modules (e-modules) integrated with numeracy literacy learning. Where math books are less able to provide delivery related to numeracy literacy. Given the lack of a learning process during the covid 19 period to improve students' abilities in the field of numeracy. The research objective is to develop an e-module for multiplication and division of numeracy literacy fractions for grade 5 elementary school students for practical problem solving. The development research method with the ADDIE model is Analysis, Design, Developments, Implementation, and Evaluation. Analysis of the data used in the form of quantitative and qualitative data analysis techniques through expert validators of teaching materials, media and language as well as teacher and student response questionnaires. The results showed that the e-module of multiplication and division of fractions based on numeracy literacy was declared feasible or valid with an average score of 89.37%. The use of e-modules got a positive response from teachers and students based on a response questionnaire with an average score of 92%. This has an effect on increasing students' understanding in the material of multiplication and division of fractions with an average value of 88. So that the e-module of multiplication and division of fractions based on numeracy literacy can help students in learning mathematics in elementary schools.